1997
DOI: 10.1063/1.474240
|View full text |Cite
|
Sign up to set email alerts
|

Luminescence spectroscopy of atomic zinc in solid rare gases. II. Temperature dependence

Abstract: The temperature dependence of the pairs of emission bands present for atomic zinc isolated in annealed solid argon, krypton, and xenon samples is examined in steady-state and time-resolved luminescence spectroscopy. The pairs of emission bands in all the Zn/RG systems exhibited a reversible temperature dependence whereby the intensity of the high-energy band decreased, while the low-energy band gained in intensity with increasing temperature. In the Zn/Ar system, the decrease in the intensity of the 218.9 nm e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

1997
1997
1999
1999

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 7 publications
1
17
0
Order By: Relevance
“…From an Arrhenius plot of the nonradiative rates extracted in the Zn-Ar kinetics study 11 it was shown that this process involved a barrier of 130.6 cm Ϫ1 . The origin of the temperature dependent interconversion of the two bands at higher temperatures will also be examined from the calculated excited-state potentials.…”
Section: Figmentioning
confidence: 99%
See 3 more Smart Citations
“…From an Arrhenius plot of the nonradiative rates extracted in the Zn-Ar kinetics study 11 it was shown that this process involved a barrier of 130.6 cm Ϫ1 . The origin of the temperature dependent interconversion of the two bands at higher temperatures will also be examined from the calculated excited-state potentials.…”
Section: Figmentioning
confidence: 99%
“…2 for an annealed sample at 9 K. Excitation into the 4p 1 P 1 -4s 1 S 0 absorption band, indicated by A in Fig. 2, produces the pair of emission bands at 219 and 238 nm labeled B and C. From lifetime measurements 10 The previously mentioned kinetics study 11 provided a wealth of information on the dynamics occurring on the excited 1 P 1 state surface of atomic zinc isolated in solid Ar. Thus on closer scrutiny of the temporal decay characteristics of the 238 nm emission it was noticed 11 that a risetime component, on the order of 0.1 ns, was present at low temperatures, TϽ13 K. Evidence for the existence of this risetime in the temporal decay profile of the C emission band is presented in Fig.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In starker contrast to the Zn-Ar system, there is also a triplet emission band at 312 nm in Zn-Kr, the intensity of which is temperature dependent. 2 Excitation into the singlet 4p 1 P 1 ←4s 1 S 0 absorption band of Zn-Xe produces no spin singlet emission at all, with emission occurring only as the pair of spin triplet bands at 356 and 399 nm.…”
Section: Introductionmentioning
confidence: 99%